Methodological research design for Industry 4.0: a service science approach - Silva, Agostinho (2021)
The challenge of this research is the conceptualisation, from the service science (S-S) perspective, of the methodological research guidelines for empirical case-studies and frameworks to describe and compare the value creation interactions of stakeholders when they evolve their operations from the current operations mode to Industry 4.0 (I4.0) mode. From the literature review we found some contact points between the pragmatist paradigm, I4.0 and service science theory. This philosophical approach is in line with the pragmatist paradigm, involving inductive and deductive logic and mixed methodology, using quantitative and qualitative approaches. The main goal is to provide a framework to better understand the problems raised from digital transformation, assuming, as much as possible, a posture that reflects social justice, collaborative networks and sustainability as basic principles.